The Presence : a ghost story - Bunting, Eve, 1928- (Graphia/Houghton Mifflin Harcourt, 2010)
While visiting her grandmother in California, seventeen-year-old Catherine comes in contact with a mysterious stranger who says he can help her contact a friend who died in a car crash for which Catherine feels responsible.